Protective effect of coenzyme Q10 against doxorubicin-induced cardiotoxicity: Scoping review article - Al Qahtani Abdullah; Al Balawi Hamed; Al Jowesim Fahad (Elsevier, 2024)
Introduction: Doxorubicin (dox) is classified as an antineoplastic antibiotic which is known as adriamycin from the anthracycline group. Due to the release of free radicals and lipid peroxidation which can cause acute cardiotoxicity. Coenzyme Q10 is found in many cells of the body, it is an antioxidant that reduces oxidative stress and lipid peroxidation. Aim: This scoping review aims to evaluate the cardioprotective effect of coenzyme Q10 in doxorubicin-induced cardiotoxicity in animals. Methods: This review was done based on Arksey and O'Malley's methodology, reviewing published articles from October 1978 and September 2023. Results: 14 out of 11,303 articles were included from the initial search, (10 out of 14 articles found that coenzyme Q10 protect has a protection effect against doxorubicin-induced cardiotoxicity). Conclusion: The results of this review found coenzyme Q10 protects against doxorubicin cardiotoxicity. It is a promising supplement that could be used to prevent cardiotoxicity induced by doxorubicin in cancer patients.